Longitudinal associations of depressive symptoms and pain with quality of life in patients receiving chronic hemodialysis. Issue 2 (18th November 2014) - Belayev, Linda Y.; Mor, Maria K.; Sevick, Mary Ann; Shields, Anne Marie; Rollman, Bruce L.; Palevsky, Paul M.; Arnold, Robert M.; Fine, Michael J.; Weisbord, Steven D.
Abstract Depressive symptoms and pain are common in patients on chronic hemodialysis (HD), yet their associations with quality of life (QOL) are not fully understood. We sought to characterize the longitudinal associations of these symptoms with QOL. As part of a trial comparing two symptom management strategies in patients receiving chronic HD, we assessed depressive symptoms using the Patient Health Questionnaire‐9 (PHQ‐9), and pain using the Short Form McGill Pain Questionnaire (SF‐MPQ) monthly over 24 months. We assessed health‐related QOL (HR‐QOL) quarterly using the Short Form 12 (SF‐12) and global QOL (G‐QOL) using a single‐item survey. We used random effects linear regression to analyze the independent associations of depressive symptoms and pain, scaled based on 5‐point increments in symptom scores, with HR‐QOL and G‐QOL. Overall, 286 patients completed 1417 PHQ‐9 and SF‐MPQ symptom assessments, 1361 SF‐12 assessments, and 1416 G‐QOL assessments. Depressive symptoms were independently and inversely associated with SF‐12 physical HR‐QOL scores (β = −1.09; 95% confidence interval [CI]: −1.69, −0.50, P < 0.001); SF‐12 mental HR‐QOL scores (β = −4.52; 95% CI: −5.15, −3.89, P < 0.001); and G‐QOL scores (β = −0.64; 95%CI: −0.79, −0.49, P < 0.001). Pain was independently and inversely associated with SF‐12 physical HR‐QOL scores (β = −0.99; 95% CI: −1.30, −0.68, P < 0.001) and G‐QOL scores (β = −0.12; 95%CI: −0.20, −0.05, P = 0.002); but not with SF‐12 mental HR‐QOL scores (β = −0.16; 95%CI: −0.050, 0.17, P = 0.34). In patients receiving chronic HD, depressive symptoms and to a lesser extent pain, are independently associated with reduced HR‐QOL and G‐QOL. Interventions to alleviate these symptoms could potentially improve patients' HR‐QOL and G‐QOL.